2018
DOI: 10.1117/1.oe.57.2.024106
|View full text |Cite
|
Sign up to set email alerts
|

Optimum display luminance depends on white luminance under various ambient illuminance conditions

Abstract: This paper reports display luminance levels for good visibility under nine ambient illuminance con

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 9 publications
1
11
0
1
Order By: Relevance
“…4 is validated with the earlier relative studies, by Xu and Zhu, 2 Lin and Huang, 14 Buchner et al, 21 etc. 1,16,48 The recommended values or models of display luminance under different ambient illumination through published ergonomic studies are included in the verification dataset for this model. The details of the model verification dataset are shown in Table 10 and Fig.…”
Section: Step3: Exponential Fitting Of the Illuminance-luminance Dimmmentioning
confidence: 99%
See 3 more Smart Citations
“…4 is validated with the earlier relative studies, by Xu and Zhu, 2 Lin and Huang, 14 Buchner et al, 21 etc. 1,16,48 The recommended values or models of display luminance under different ambient illumination through published ergonomic studies are included in the verification dataset for this model. The details of the model verification dataset are shown in Table 10 and Fig.…”
Section: Step3: Exponential Fitting Of the Illuminance-luminance Dimmmentioning
confidence: 99%
“…13 Validation of the proposed model by earlier studies. 1,2,14,16,21 luminance ranged from 3.1 to 200.0 cd∕m 2 , and the ambient illumination from 200 to 800 lx.…”
Section: Effects Of Ambient Illuminance and Display Luminance On Eachmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, their experiments showed that these luminance levels vary with color, polarity, and image content. Another perspective on the relevant topic was also introduced to find an optimum luminance for display under different illuminations in terms of visibility and power consumption [5] . The authors claimed that the luminance levels for indoor use between 200 and 500 cd / m 2 would be satisfactory.…”
Section: Introductionmentioning
confidence: 99%